217k views
4 votes
Divide -3x^3-2x^2-x-2 by x-2

User Sarah Remo
by
5.3k points

1 Answer

7 votes

Let's do this by Briot-Ruffini


First: Find the monomial root


x - 2 = 0

x = 2


Second: Allign this root with all the other coeficients from equation

Equation = -3x³ - 2x² - x - 2

Coeficients = -3, -2, -1, -2

2 | -3 -2 -1 -2


Copy the first coeficient


2 | -3 -2 -1 -2

-3


Multiply him by the root and sum with the next coeficient


2.(-3) = -6

-6 + (-2) = -8


2 | -3 -2 -1 -2

-3 -8


Do the same


2.(-8) = -16

-16 + (-1) = -17


2 | -3 -2 -1 -2

-3 -8 -17


The same,


2.(-17) = -34

-34 + (-2) = -36


2 | -3 -2 -1 -2

-3 -8 -17 -36


Now you just need to put the "x" after all these numbers with one exponent less, see


2 | -3x³ - 2x² - 1x - 2

-3x² - 8x - 17 -36


You may be asking what exponent -36 should be, and I say:


None or the monomial. He's like the rest of this division, so you can say:


(-3x³ - 2x² - x - 2)/(x - 2) = -3x² - 8x - 17 with rest -36 or you can say:

(-3x³ - 2x² - x - 2)/(x - 2) = -3x² - 8x - 17 - 36/(x - 2)


Just divide the rest by the monomial.

User Aron Rotteveel
by
6.1k points